3.(-x+1)=5-4x
por favor me ajudem
mariaantoniaa895:
Depois VC pode me ajudar
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
3(-x + 1) = 5 - 4x
-3x + 3 = 5 - 4x
-3x + 4x = 5 - 3
x = 2
Respondido por
2
Resposta:
x = 2
Explicação passo a passo:
3 (-X + 1) = 5 - 4x
-3x + 3 = 5 - 4x
-3x + 4x = 5 - 3
X = 2
Perguntas interessantes
Matemática,
7 meses atrás
Inglês,
7 meses atrás
Artes,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás